Procollagen-lysine 2-oxoglutarate 5-dioxygenases are responsible for 5R-hydroxylysine modification of therapeutic T-cell bispecific monoclonal antibodies produced by Chinese hamster ovary cells - Bauer, Niels; Boettger, Marco; Papadaki, Styliani; Leitner, Tanja; Klostermann, Stefan; Kettenberger, Hubert; Georges, Guy; Larraillet, Vincent; Gluhacevic von Kruechten, Dino; Hillringhaus, Lars; Vogt, Annette; Ausländer, Simon; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
We present a detailed mass spectrometric analysis of three 2+1 T-cell bispecific monoclonal antibodies (TCB mAbs), where an unexpected +15.9950 Da mass shifts in tryptic peptides was observed. This modification was attributed to the occurrence of 5R-hydroxylysine (Hyl) using a hybrid LC-MS/MS molecular characterization and CRISPR/Cas9 gene deletion approach. The modification was found at various sites within the TCB mAbs, with a conspicuous hotspot motif mirroring a prior observation where Hyl was mapped to the CH1-VH Fab domain interface of IgGs. In contrast to the preceding report, our structural modeling analysis on TCB mAbs unveiled substantial differences in the orientation and flexibility of motifs in immediate proximity and across the artificial CH1-VL cross Fab interface and the upstream elbow segment. Utilizing a hybrid database search, RNAseq, and a CRISPR/Cas9 knock-out methodology in Chinese hamster ovary (CHO) production cell lines, procollagen-lysine 2-oxoglutarate 5-dioxygenases (PLODs) were conclusively identified as the catalyzing enzymes accountable for the 5R-Hyl modification in TCB mAbs. To inhibit Hyl formation in TCB mAbs quantitatively, the activity of all three Chinese hamster PLOD isoenzymes are needed to be depleted by CRISPR/Cas9 gene knock-out. Moreover, our investigation identified cell culture iron availability, process duration, and clonal variability in CHO cells as elements influencing the levels of Hyl formation in TCB mAbs. This research offers a solution for circumventing Hyl formation in therapeutic complex mAbs formats, such as TCB mAbs, produced in CHO cell culture processes to address potential technical and biological challenges associated with unintended Hyl modification.